Lateral branch induction at nursery with growth regulators in ‘maxi gala’ apple trees grafted on four rootstocks - Marchioretto L.D.R.* (2019)
© 2019 Elsevier B.V.Apple production in Southern Brazil has been increasing along the past decade, and part of this was due to the introduction of more adapted dwarfing rootstocks and consequently increased tree density in the orchards. Looking for obtaining early beariness, the use of branched nursery trees is one of the most important steps. The objective of this experiment was to determine the effects of plant the growth regulators Benzyladenine (BA), Benzyladenine + Gibberellic acid4+7, Thidiazuron, and Cyclanilide + Ethephon on the induction of lateral branches of ‘Maxi Gala’ apple trees at nursery, grafted on the rootstocks G.202, G.213, M.9, and Marubakaido with M.9 interstem. The growth regulators Benzyladenine (BA), and Benzyladenine + Gibberellic acid4+7 are the most effective on improving tree's architecture and on increasing the number of spurs, for all scion-rootstock combinations tested. Plant growth regulators at elevated doses strongly interrupt apical dominance and stimulate an elevated number of lateral branches with narrower crotch angles.